Implementasi Algoritma C4.5 Untuk Mengukur Tingkat Kepuasan Mahasiswa yang Berlangganan Wifi Indihome - Kiswara, Qodrat; Safii, M.; Andani, Sundari Retno; Lubis, Muhammad Ridwan; Renaldi, Renaldi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The urgency of research on satisfaction levels is closely related to the success and desires of a business or organization. Without a good understanding of customer satisfaction, a company or organization may lose market share, face declining sales, or even face failure. Therefore, this research must be carried out regularly and continuously. The purpose of this research is to determine the level of customer satisfaction and to determine the dominant service quality that influences the quality of service provided by PT Telkom Indihome to customers. In this research, researchers used the C4.5 Algorithm data mining technique. The research data source used was by making observations and distributing questionnaires to customers of PT Telkom Pematangsiantar City. In this case, researchers used assessment attributes, namely service quality, accessibility and product quality. This research is expected to provide information and input to PT Telkom Indihome in the form of evaluations in improving network quality. The results of the research conducted by the author obtained the following conclusion, namely that Data Mining with the C4.5 Algorithm can classify the measurement of satisfaction levels of STIKOM Tunas Bangsa students who subscribe to Indihome WiFi. The accuracy results obtained by this research were 75.00% with the average student who subscribed to Indihome WiFi stating that they were satisfied.